PENGELOLAAN DAN PENDAMPINGAN REMAJA DI ERA MILENIAL - WAHYUNITA SARI; Titi Alfiani; Septi Tri Aksari (JPS : Jurnal Pengabdian Serulingmas, 2022)
Adolescence is a transitional period marked by many changes, both anatomically, physiologically, intellectually, and emotionally as well as relationships in the social environment. These changes can affect the psychosocial development of adolescents, especially in the ability to manage conflicts that make adolescents experience stress. Some teenagers divert stress by doing habits such as smoking, consuming alcohol, overeating, using drugs, pornography to sexual deviations. The community service activity on "Management and Assistance of Youth in the Millennial Era" is one of the information media that can suppress pornography, abuse of narcotics and drugs and manage adolescent stress.